2013
DOI: 10.3856/vol41-issue5-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del fotoperiodo y la razon camaron:macroalga en la remoción de nitrogeno amoniacal total por Gracilaria vermiculophylla, en cultivo con Litopenaeus vannamei, sin recambio de agua

Abstract: Efecto del fotoperiodo y la razón camarón:macroalga en la remoción de nitrógeno amoniacal total por Gracilaria vermiculophylla, en cultivo con Litopenaeus vannamei, sin recambio de agua ), N-NO 2 (0.145 ± 0.29 mg L -1 ) y N-NO 3 (3.13 ± 0.73 mg L -1 ) were registered in the biomass rate of 1:8. The highest growth rates of the macroalgae (3.07 ± 1.44% day -1 ) were recorded with 24:00 h photoperiod and biomass ratio 1:8. The highest rate of N incorporation (0.31 ± 0.12 mg N L -1 ) of the macroalgae occurred un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…The TAN and NO 2 ‐N removal by Gracilaria in water with zero exchange has been shown to depend on the photoperiod (16:8 light/dark for TAN and 14:10 light/dark NO 2 ‐N), and the biomass ratio of shrimp:seaweed of 1:8 (Sánchez‐Romero et al . ). In the end of the experiment, the biomass ratios of shrimp:seaweed were 1:1.28 (IBS 2.5), 1:2.75 (IBS 5.0) and 4.36 (IBS 7.5), whereas light intensity was kept at ~1000 lux with a natural photoperiod.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The TAN and NO 2 ‐N removal by Gracilaria in water with zero exchange has been shown to depend on the photoperiod (16:8 light/dark for TAN and 14:10 light/dark NO 2 ‐N), and the biomass ratio of shrimp:seaweed of 1:8 (Sánchez‐Romero et al . ). In the end of the experiment, the biomass ratios of shrimp:seaweed were 1:1.28 (IBS 2.5), 1:2.75 (IBS 5.0) and 4.36 (IBS 7.5), whereas light intensity was kept at ~1000 lux with a natural photoperiod.…”
Section: Discussionmentioning
confidence: 97%
“…The poor assimilation of nutrients (nitrogen and phosphorus) by shrimp can be compensated by the presence of red seaweed Gracilaria , which can turn wastes into biomass, significantly improving water quality in traditional systems (Huo, Xu, Wang, Zhang, Zhang, Wu, Chen & He ; Marinho‐Soriano, Azevedo, Trigueiro, Pereira & Carneiro ; Huo, Wu, Chai, Xu, Han, Dong & He ; Robledo, Navaro‐Angulo, Lozano & Freile‐Pelegrin ) and zero‐exchange systems (Sánchez‐Romero, Miranda‐Baeza, López‐Elías, Martínez‐Córdova, Tejeda‐Mansir & Márquez‐Ríos ; Brito, Arantes, Magnotti, Derner, Pchara, Olivera & Vinatea ). Seaweed may also improve shrimp growth and yield in semi‐intensive (Gamboa‐Delgado, Peña‐Rodríguez, Ricque‐Marie & Cruz‐Suárez ; Portillo‐Clark, Casillas‐Hernández, Servín‐Villegas & Magallón‐Barajas ) and intensive systems (Brito, Arantes et al .…”
Section: Introductionmentioning
confidence: 99%
“…No effect from the use of an integrated biofloc system was observed on dissolved inorganic nitrogen removal, probably due to a lower photoperiod (12:12 light/dark), and lower biomass rate of shrimp:seaweed (1.27 -1.79) than those used by Sánchez-Romero et al (2013) (12:12 light/dark and shrimp:seaweed 1:8), and higher TSS levels of about 500 mg/L as compared to Brito et al (2016), who used 223 to 253 mg/L.…”
Section: Discussionmentioning
confidence: 96%
“…Limited studies in the scientific literature have focused on nitrogen dynamics in integrated recirculating aquaculture systems (RASs) determined by a modeling approach, and most of the related research included different biological and physical conditions than those studied here. Here, a comprehensive model including shrimp, macroalgae, and bacterial populations was developed and calibrated, and the parameters were obtained from an integrated culture of macroalgae and shrimp conducted by the authors Sánchez‐Romero et al (, ) and from parameters found in the literature and calibrated within the reported ranges (Tables and ).…”
Section: Discussionmentioning
confidence: 99%